100% kid portrait photography studio lighting, posing, and directing : over 90 minutes of training presented in high-definition video - Jones, Allison (Peachpit Press, 2014)
"Pro photographer Allison Tyler Jones provides inspiration and practical techniques for photographers to authentically capture kids during a typical 60-minute studio session. In video, Allison approaches studio lighting specifically for kids with a mix of technical information and easy-to-follow steps for both the preparation and working with subjects who are shy, naughty, showing off, or constantly in motion. Allison's style is spontaneous and natural. And the expressions she captures are knowing and timeless. Her unique teaching style of breaking down complicated lightening scenarios, providing simple styling and direction techniques, and placing the child and their personality at the center of the shot is a winning combination."--Resource description page.